Gangguan Neurologis Pasca-COVID-19 - Lukito, Patricia Michelle; Wreksoatmodjo, Budi Riyanto (Cermin Dunia Kedokteran, 2024)
Post-COVID-19 neurological disorders, also known as post-covid neurology syndrome (PCNS), are an integral part of long COVID and include various health problems that can last for several weeks, several months, or even years. These neurological disorders can vary, such as postCOVID fatigue syndrome, ognitive impairment, anosmia and ageusia, headaches, or diseases such as stroke and GBS, which still require further research on the mechanisms. Until now, there has been no definitive diagnostic examination, so the history and physical examination must be precise. Further management is given according to the complaint.